Pegadaian Syariah Prenduan Sumenep Branch Strategy for Increasing Customer Interest - Supriyadi Supriyadi; Muhammad Syaiful Islam Al-Khair (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Every institution must carry out a promotional strategy to attract customers to want to use these products. Pegadaian Syariah Prenduan branch is one of the Islamic financial institutions that carries out promotional strategies in increasing customer interest, namely by installing benner at every point, gathering, providing cashbacks or coupon draws with prizes, this needs to be reviewed to combine with the promotion theory proposed by Kotler and Armstrong that the promotional mix as a marketing communication medium, has several main activities, namely advertising,  personal sales, sales promotion and publicity. In Pegadaian Syariah Prenduan Branch from 2019-2021 decreased, but there was an increase in 2022. The approach in this study uses a qualitative approach. This type of research is field research. Field research is a research that is carried out intensively, in detail, and in depth on a certain object by studying it as a case. The data sources in this study are interviews, observations and documentation. The targets and locations are used as research sites at the Prenduan branch of Pegadaian Syariah. The promotion strategy of Pegadaian Syariah Prenduan branch in increasing customer interest is 1. Advertising, Personal Sales, Publicity, Sales Promotion in sales promotion has a special strategy to increase customer interest, namely providing cashbacks or lucky draw coupons. In addition, in carrying out a promotion strategy, there are also factors that become obstacles, namely: 1. Lack of customer understanding of social media, 2. Time to promote, 3. Weather conditions.